Engagement and follower growth: Social media strategies of Swiss athletes at the Paris Olympics - Staley, L.; Droux, F. (Current Issues in Sport Science, 2025)
Introduction Social media platforms enable athletes to market themselves and engage with the public, bypassing traditional media gatekeepers. Understanding the factors driving engagement and follower growth on social media during high-visibility events is critical for athletes to leverage their athletic performance for brand growth and endorsement opportunities (Bredikhina et al., 2023; Su et al., 2020). This study investigates how athletic performance and social media behavior influence engagement and follower growth on Instagram among Swiss athletes during the Summer Olympic Games in Paris 2024.